Guidelines for treatment of umbilical and epigastric hernias from the European Hernia Society and Americas Hernia Society. Issue 3 (9th January 2020) - Henriksen, N A; Montgomery, A; Kaufmann, R; Berrevoet, F; East, B; Fischer, J; Hope, W; Klassen, D; Lorenz, R; Renard, Y; Garcia Urena, M A; Simons, M P
Abstract: Background: Umbilical and epigastric hernia repairs are frequently performed surgical procedures with an expected low complication rate. Nevertheless, the optimal method of repair with best short- and long-term outcomes remains debatable. The aim was to develop guidelines for the treatment of umbilical and epigastric hernias. Methods: The guideline group consisted of surgeons from Europe and North America including members from the European Hernia Society and the Americas Hernia Society. The Grading of Recommendations, Assessment, Development and Evaluation (GRADE) approach, the Scottish Intercollegiate Guidelines Network (SIGN) critical appraisal checklists, and the Appraisal of Guidelines for Research and Evaluation (AGREE) instrument were used. A systematic literature search was done on 1 May 2018, and updated on 1 February 2019. Results: Literature reporting specifically on umbilical and epigastric hernias was limited in quantity and quality, resulting in a majority of the recommendations being graded as weak, based on low-quality evidence. The main recommendation was to use mesh for repair of umbilical and epigastric hernias to reduce the recurrence rate. Most umbilical and epigastric hernias may be repaired by an open approach with a preperitoneal flat mesh. A laparoscopic approach may be considered if the hernia defect is large, or if the patient has an increased risk of wound morbidity. Conclusion: This is the first European and American guideline on the treatment of umbilical and epigastric hernias. It is recommended that symptomatic umbilical and epigastric hernias are repaired by an open approach with a preperitoneal flat mesh. Graphical Abstract: This guideline evaluates the management of umbilical and epigastric hernias. How to fix them